Simulation of primary atomization due to Kelvin-Helmholtz instability - Kazimardanov, Maxim Georgievich; Mingalev, Stanislav Victorovich; Lubimova, Tatjana Petrovna; Gomzikov, Leonid.Yurjevich (Computational Continuum Mechanics, 2017)
Application of a volume of fluid method to the atomization due to Kelvin-Helmholtz instability is studied. The aim of the work is to develop an approach for modeling the primary breakup using the volume of fluid method, to investigate the grid convergence and to choose the optimal size of grid cell, and to calculate the primary breakup of the film in the channel by high-speed airflow using the obtained approach. The dependences of the average values of the angle of attack, the velocity modulus and the Sauter mean droplet diameter on the longitudinal coordinate of the channel are obtained. The step-by-step averaging over the ensemble of droplets and over time allows us to get smooth coordinate dependences of the characteristics of the droplet ensemble. It has been found that there is no reason to decrease cell size in order to obtain an accurate description of fine droplets. The number of such droplets increases rapidly with decreasing cell size, but their contribution to the average characteristics of the droplet ensemble remains insignificant. Moreover, the Sauter mean diameter, which was found by the volume of fluid method, is close to the theoretical value of this quantity. The dependence of the Sauter mean diameter on the thickness of the liquid layer agrees qualitatively with the dependence found in the experiment.
Keywords: Kelvin-Helmholtz instability; volume of fluid method (VOF); 2D flow; atomization; Sauter mean diameter